The impact of the assimilation of migrants on the well-being of native inhabitants: A theory - Oded Stark; Jakub Bielawski; Marcin Jakubek (University of Bonn, Center for Development Research (ZEF), 2015)
We present a theory that systematically and causally links the well-being of native inhabitants with variation in the extent of the assimilation of migrants. Recent empirical findings are yielded as predictions of the theory.
Keywords: I31; J61; 330; migrants' assimilation; the well-being of native inhabitants